Firm-to-firm trade networks: A focus on Latin America and the Caribbean - Vanessa Alviarez; Juan S. Blyde (Inter-American Development Bank (IDB), 2025)
Trade flows are the result of the interaction between buyers and sellers. Understanding how these firm-to-firm relationships form, survive, and evolve over time helps identify how countries can improve their export outcomes. Using a very granular dataset of United States import transactions from all countries around the world, we present a battery of static and dynamic metrics of firm-to-firm relationships. We show how Latin American exporters compare with exporters from other regions across all the metrics. We show that trade costs negatively affect the formation and duration of firm-to-firm networks. Regional differences in these costs partially explain Latin Americas performance. The study discusses a series of measures to reduce trade-related cots in the region that, in light of the results, are likely to improve the trade networks of Latin American countries.
Keywords: F12; F14; L22; 330; Trade networks; Supply chains; Exports